On a class of boundary value problems in the theory of surface waves - Lukovsky , I. A.; Timokha , A. N. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
Boundary value problems are formulated concerning characteristic oscillations relative to capillary-sound equilibrium forms and theorems are established concerning properties of spectra of these problems; theorems are also presented concerning stability of the indicated forms of equilibrium.